Fine‐needle aspiration of parathyroid adenomas: Indications as a diagnostic approach. Issue 1 (24th August 2020) - Suzuki, Ayana; Hirokawa, Mitsuyoshi; Kanematsu, Risa; Tanaka, Aki; Yamao, Naoki; Higuchi, Miyoko; Hayashi, Toshitetsu; Kuma, Seiji; Miya, Akihiro; Miyauchi, Akira
Abstract: Background: We aimed to determine the indication of fine‐needle aspiration (FNA) for parathyroid adenoma (PA)‐suspected nodules and the cytological features of PA, and to discuss the ancillary techniques for diagnostic confirmation. Method: Clinical, cytological, and histological examinations of 15 PA patients (4.0% of all PA resected patients) were conducted through FNA on 16 nodules. We also examined the cytological preparations of 10 follicular neoplasms (FNs) and 10 poorly differentiated thyroid carcinomas (PDTCs). Results: FNA was performed to detect PA in nine (56.3%) nodules. The remaining seven (43.8%) nodules underwent FNA for lesions considered as thyroid nodules or lymph nodes. The levels of parathyroid hormone (PTH) in the aspiration needle washout fluid were observably high, except for that from one nodule with unsatisfactory FNA. Cytologically, the incidences of wedge pattern (86.7%) and salt and pepper chromatin (86.7%) in PAs were significantly higher than in FNs and PDTCs. In contrast, the appearance of colloid globules and nuclear grooves was less frequent than that of FNs and PDTCs. GATA‐3 expression was intense in all PAs that immunocytochemistry were performed. Histologically, capsular invasion and/or laceration, tumor seeding, granulation tissue, and fibrosis were observed. Conclusions: When PA localization is unusual or inconclusive despite extensive imaging, FNA may be performed. We asserted that wedge pattern, salt and pepper chromatin, and the absence of colloid globules and nuclear grooves are diagnostic cytological indicators of PA rather than of FN or PDTC. We recommend PTH measurements using needle washout fluid for PA‐suspected nodules, and immunocytochemistry with the GATA‐3 antibody for cytologically PA‐suspected nodules.